Religious Moderation as a National Defense Effort to Exclusivism, Extremism, and Terrorism: Concept and Implementation - Armita, Pipin; Karuok, Mohamad Azmi (Al-Wasatiyah: Journal of Religious Moderation, 2022)
This study discusses how to instill an attitude of religious moderation as an effort to ward off exclusivism, extremism, and terrorism. Through this paper, the author would like to offer an offer that in terms of national resilience, through an attitude of religious moderation, every human being will be able to control himself not to commit violence, which leads to exclusivism, extremism, and terrorism. This research uses a descriptive analysis approach with a data documentation method. With this approach, the author tries to describe the meaning of national resilience and describes the concept of religious moderation to be used as a critique of the eradication of exclusivism, extremism, and terrorism. Descriptive analysis in this study was carried out by reading, observing, and understanding the texts of the results of studies on exclusivism, extremism, and terrorism. Furthermore, the author tries to observe and define religious moderation as a basic concept, then the concept is analyzed and translated into the terminology of national security. The results of this study are known that in terms of national security, to counteract exclusivism, extremism, and terrorism is to instill an attitude of religious moderation. Although there are actually many other steps, religious moderation is a preventive measure in responding to exclusivism, extremism, and terrorism.